Zero correlation-integral attack of MIBS block cipher - Qing-cong LIU; Ya-qun ZHAO; Meng MA; Feng-mei LIU (Tongxin xuebao)
MIBS is a lightweight block cipher for extremely constrained environments such as RFID tags and sensor networks. The MIBS algorithm's ability to resist zero correlation-integral analysis was evaluated. An 8-round zero corre-lation linear distinguisher of MIBS was given. Then, a 8-round distinguisher of MIBS was founded by using relationship between zero-correlation linear distinguisher and integral distinguisher. Finally, considering the symmetrical structure of the MIBS and using the partial-sum technique, it applied integral attack to 10 and 12 rounds of MIBS-80. The time com-plexities of 10 and 12 round attack on MIBS-80 are 227.68and 248.81. The data complexity is 248.